REFLEKSI KECEMASAN DALAM FILM FINAL DESTINATION 3 KARYA JAMES WONG - Karauwan, Matthew Zico; Wantasen, Isnawaty L.; Rambing, Rosalina R. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACT This research entitled ?The Reflection of Anxiety in the Film ?Final Destination 3? by James Wong,? is written to identify, classify, and analyze the types of anxiety found in the film Final Destination 3. Anxiety is a self effective, unpleasant state, accompanied by a physical sensation that warn the person against impending danger, and there are other feelings of unpleasant character (mental tension, sorrow, grief), and anxiety must have other characteristics beside this quality of unpleasure (Freud, 1996:69). This study aims at identifying, classifying, and analyzing the types of anxiety based on Freud?s theory of anxiety and Snyder?s theory of mise-en-scene and cinematography. The method used in this study is a qualitative descriptive method by Bogdan and Bilken (1982). The data were taken from the movie entitled Final Destination 3. All the collected data were identified, classified, and analyzed by using Freud theory (1996) and Snyder (2011). The result of this research show that there are 31 anxiety reflected in the movie, consisting 16 reality anxiety, 10 neurotic anxiety, and 5 moral anxiety. Keywords: Anxiety, Reality, Neurotic, Moral, Final Destination 3